Survey Study of Cutaneous Leishmaniasis in Baghdad - Turki, Wasan Qasim; Reda, Jaafar Iyad Abdel; Abbas, Reham Hussam; Rdaali, Ali Reza Riad Fatek (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2022)
The research included an epidemiological study of cutaneous leishmaniasis in Baghdad for two years (2019 and 2020). Data were collected from the Iraqi Ministry of Health in Baghdad public health departments for Al-Karkh and Al-Rusafa districts. The results of the positive examinations for cutaneous leishmaniasis for the two years mentioned came with 54 infections in Al-Rusafa district and 80 infections in Al-Karkh district for the year 2019, while in 2020, the infections in Al-Rusafa district were 201 infections and 152 infections in Al-Karkh district. The data were divided in terms of gender into males and females, so the percentage for the year (2019) was 15% for males and 12% for females, and in (2020) 44% for males and 29% for females. Data were divided according to their age received from their sources. On their basis, they were divided into seven groups and according to years; they are as the following: [(1-9) 5.13% for the year 2019 and 16.63% for the year 2020,(10-19) 4.31% for the year 2019 and 11.09% for the year 2020,(20- 29) 6.77% for the year 2019 and 10.88% for the year 2020, (30-39) 5.13% for the year 2019 and 11.70% for the year 2020,(40-49) 2.05% for 2019 and 9.45% for 2020,(50-59) 2.05% for the year 2019 and 7.8% for the year 2020,(59+) 2.05% for 2019 and 4.93% for 2020].